2006
DOI: 10.1080/09585190600697638
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on line managers in human resource management: Hilton International's UK hotels

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 29 publications
3
77
1
1
Order By: Relevance
“…Maxwell and Watson 2006;Perry and Kulik, 2008). While this is a global trend, relatively little is known about its impact on the effectiveness of people management in general Perry and Kulik 2008), and employee career management in particular.…”
mentioning
confidence: 99%
“…Maxwell and Watson 2006;Perry and Kulik, 2008). While this is a global trend, relatively little is known about its impact on the effectiveness of people management in general Perry and Kulik 2008), and employee career management in particular.…”
mentioning
confidence: 99%
“…A study of 760 LMs from Hilton hotels throughout the UK found heavy workloads and short time pressures were two key challenges for LMs undertaking their HRM role (Maxwell & Watson, 2006). Another study undertaken by Nehles et al (2006) indicated four factors contributed to role conflict among LMs: capacity, competencies, support and policies and procedures.…”
Section: Role Theorymentioning
confidence: 99%
“…Cunningham & Hyman, 1995;Whittaker & Marchington, 2003;Yusoff, Abdullah, & Ramayah, 2010). Little attention has been paid to other sectors, such as service and tourism (Maxwell & Watson, 2006). Thus, exploring what happens in other sectors may enhance the understanding of the LMs' HRM role development and their contribution in various fields.…”
mentioning
confidence: 99%
“…In addition, coherent systematic support provided by HR specialists and the training of line managers is crucial as some of the latter may lack the appropriate skills for supervising their staff and implementing HRM practices in an effective way. However, Maxwell and Watson (2006) assert that the challenge for line managers and HR specialists does not just rest upon their relationship quality, for it also depends upon the ability and willingness of the former to carry out HR tasks properly (Renwick and MacNeil;2002:407). Consequently, improvement of the relationship between line managers and HR specialists will motivate the former to use their knowledge and skills for effective HR.…”
Section: Proposition 4 Greater Top Management Support For Effective mentioning
confidence: 99%
“…Consequently, there have been increasing calls for line managers to act as business partners in conjunction with HR and other employees regarding HR processes (Renwick,003). In effect, HRM implementation by line managers in relation to their subordinates' employment issues has become increasingly commonplace in recent years (Bos-Nehles, Van Riemsdijk, Looise, 2013;Maxwell & Watson, 2006). Renwick (2003) notes that significant numbers of line managers want to get involved in sharing HR responsibilities with HR specialists, and that they take these responsibilities very seriously.…”
Section: Introductionmentioning
confidence: 99%